Cryo-EM structure of the chloroplast ribosome - Tofayel Ahmed (2018)
Ribosomes are the universal machines which perform mRNA translation inside the cell. Chloroplasts harbor bacterial-like 70S ribosome but have acquired five plastid-specific ribosomal proteins (PSRPs) namely cL37, cL38, cS22, cS23 and bTHXc, extensions in the plastid ribosomal proteins (PRPs) and rRNA expansions and deletions. Here, a complete structure of the 70S spinach chloroplast ribosome (cp-ribosome) has been determined using cryo-electron microscopy and single particle analysis. The structures of the large (LSU) and small subunits (SSU) are resolved to 3.3 and 3.7 Å, respectively, demonstrating that the overall architecture of cp-ribosome is similar to the bacterial counterpart. The localization and modeling of the PSRPs, PRP-extensions and remodeled rRNAs suggest about the probable functions of these altered elements in the contexts of cp-ribosome structure and translation regulation inside chloroplasts. The mode of interaction of the hibernation factor, plastid pY, which is present at the subunit interface is also discussed.